2014
DOI: 10.1371/journal.pone.0104454
|View full text |Cite
|
Sign up to set email alerts
|

Response of Two Dominant Boreal Freshwater Wetland Plants to Manipulated Warming and Altered Precipitation

Abstract: This study characterized the morphological and photosynthetic responses of two wetland plant species when they were subject to 2–6°C fluctuations in growth temperature and ±50% of precipitation, in order to predict the evolution of natural wetlands in Sanjiang Plain of North-eastern China. We investigated the morphological and photosynthetic responses of two dominant and competitive boreal freshwater wetland plants in Northeastern China to manipulation of warming (ambient, +2.0°C, +4.0°C, +6.0°C) and altered p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Changes in temperature can have pervasive effects on the structure and function of freshwater wetland ecosystems ( Hamilton, 2010 ). Wetland plant growth and photosynthesis efficiency increase with increasing temperatures within a certain range, increasing nutrient uptake and conversion ( Zou et al, 2014 ). However, excessively high temperatures may reduce the germination of plant seeds and incubation of animals, which can have serious effects on wetland plant and microbial communities, disrupting wetland biodiversity ( Nielsen et al, 2015 ).…”
Section: Environmental Drivers Of Functional Stability In Freshwater ...mentioning
confidence: 99%
“…Changes in temperature can have pervasive effects on the structure and function of freshwater wetland ecosystems ( Hamilton, 2010 ). Wetland plant growth and photosynthesis efficiency increase with increasing temperatures within a certain range, increasing nutrient uptake and conversion ( Zou et al, 2014 ). However, excessively high temperatures may reduce the germination of plant seeds and incubation of animals, which can have serious effects on wetland plant and microbial communities, disrupting wetland biodiversity ( Nielsen et al, 2015 ).…”
Section: Environmental Drivers Of Functional Stability In Freshwater ...mentioning
confidence: 99%
“…A narrow sandy ridge on the northern shore is separated from Lake Xingkai and forms a smaller lake named Xiaoxingkai that belongs to China. At Lake Xingkai, the annual mean precipitation is 561 mm, and the mean temperature is 3.5 • C [22]. The Fe concentration of the lake water can be as high as 0.62 mg·L −1 and is the highest concentration found among the waters in the Heilongjiang River system [23].…”
Section: Sampling Site and Soil Core Samplingmentioning
confidence: 99%
“…Breeuwer et al ( 2008 ) found an increase in plant height for Sphagnum species, but a similar response was not found for salt marsh species (Charles & Dukes, 2009 ). Studies of leaf area on two boreal wetland plants found no or even negative effects of warming (Zou et al, 2014 ), whereas Moor et al ( 2015 ) found that warming increased the abundance of fast‐growing plants with larger leaves, a difference that could affect key ecosystem services such as flood attenuation and short‐term nutrient retention. The relative abundance of growth forms and effects of increased temperature also differed depending on wetland type where increasing temperature in peatlands favored graminoid growth, while shrub cover increased in bogs (Dieleman & Branfireun, 2015 ; Weltzin et al, 2003 ).…”
Section: Introductionmentioning
confidence: 99%